2020
DOI: 10.1093/europace/euaa250
|View full text |Cite
|
Sign up to set email alerts
|

Reprocessing of electrophysiology material in EHRA countries: an EHRA Young EP survey

Abstract: Data on reprocessing of electrophysiology (EP) materials are sparse. Reprocessing of catheters and other materials in daily routine varies through countries and may depend on specific material characteristics, supplier, or federal law. The aim of this study was to collect data on reprocessing usage through EHRA countries. An online survey consisting of 27 questions was distributed to EHRA Young EP members and members of national EP working groups. Two hundred and two participants from 34 EHRA countries complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Despite this, due to their high cost these catheters are reused not just in low income countries but also in many European and North American centres. [1][2] This reuse is supported by extensive literature showing safety in reusing these catheters.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Despite this, due to their high cost these catheters are reused not just in low income countries but also in many European and North American centres. [1][2] This reuse is supported by extensive literature showing safety in reusing these catheters.…”
mentioning
confidence: 77%
“…1 A 2021 publication surveyed respondents from 34 European countries and found that around two thirds of the electrophysiologists had experience with resterilized equipment and the majority would be using reprocessed ablation and diagnostic catheters. 2 However there is no uniform regulation regarding reprocessing in EU. Spain, Italy, France have banned this.…”
Section: International Practicesmentioning
confidence: 99%
“…This sustainable cost-reduction strategy could help enable development of arrhythmia services in LMICs. 84 , 85 , 86 , 87 , 88 , 89 Limited studies demonstrate safety of ablation and mapping catheters, with the Food and Drug Administration determining no increased risk to health from use of remanufacturing. 88 No incidents of prion transmission attributed to use of a reconditioned EP catheter has been identified to date, with the caveat that prion infection may remain indolent for decades.…”
Section: Opportunities To Build Arrhythmia Treatment Capacity In Reso...mentioning
confidence: 99%
“…Опитування інтервенційних кардіологівчленів European Heart Rhythm Association (EHRA), проведене онлайн у 2020 р., виявило, що 53 % респондентів повторно використовували одноразові інструменти, а європейські інтервенційні електрофізіологи вважають таке використання загалом безпечним та економічно ефективним. З огляду на потенційні фінансові та екологічні переваги переробки, а також законодавчі вимоги протягом останніх десятиліть, необхідні актуальні та надійні дані щодо безпечності та економічної ефективності повторного використання [18].…”
Section: дискусії та обговоренняunclassified